Photoreduction of CO2 to Formic Acid in Aquatic Phase Using Layer Double Hydroxide (LDH) Catalyst - Rizkiana, Jenny; Auliardi, Dzaky; Az Zahra, Aghietyas Choirun; Thadeo, Francesco; Saputera, Wibawa Hendra; Soerawidjaja, Tatang Hernas; Devianto, Hary (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
The increasing accumulation of CO2, the primary greenhouse gas (GHG), in the Earth's atmosphere has caused significant environmental problems and adverse climate change. Photoreduction offers promising method to convert CO2 into high value chemical compounds, such as formic acid, which can serve as a hydrogen carrier. The process of photoreduction efficiency can be enhanced by using photocatalyst capable of operating across two distinct photosystems each having a different spectrum based on the sensitivity of light. This study aims to investigate the impact of the photocatalyst preparation conditions on the activity of the resulting photocatalyst and identify which is the most effective one on the formic acid production. Photocatalysts based on Layered Double Hydroxide (LDH) composed of zinc and chromium was synthesized, resulting in Zn-Cr LDH, which was subsequently enhanced by incorporating Cu and Cu₂O. The operating temperature varied at 60 ℃ and 100 ℃. The highest yield of formic acid of 21,62 μmol.gcat-1.hr-1 was obtained at a reaction temperature of 100 ℃ using 0.3Cu@Zn-Cr LDH. This photocatalyst shows increased activity when the reaction temperature is increased to 60 ℃ and 100 ℃. In contrast, 0.3Cu2O@Zn-CrLDH showed a decreased activity at the elevated temperatures. This discrepancy attributed to the self-oxidation mechanism of Cu and Cu2O; while the oxidation of 0.3Cu@Zn-CrLDH results in Cu2O which retains photocatalytic activity, the oxidation of 0.3Cu2O@Zn-CrLDH leads to inactive CuO. This study provides valuable insight into the material design and demonstrates the potential of Cu-modified Zn-Cr LDH for sustainable CO2 reduction applications. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).